Dr Claude Massin (25/08/1948—04/09/2021), in Memoriam - Samyn, Yves (Zootaxa, 2021)
This contribution provides an overview of the scientific career of the late Dr Claude Massin (1948–2021), listing his scientific activities (academic career, participation to and organization of expeditions and scientific conferences, publications) as well as the taxa he described as new to science and the eponyms that were dedicated to him. The scientific career of Claude Massin is briefly sketched against the background of the personal family-life.